2022
DOI: 10.3390/ijms23158589
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization in Bioartificial Parenchymal Tissue: Bioink and Bioprinting Strategies

Abstract: Among advanced therapy medicinal products, tissue-engineered products have the potential to address the current critical shortage of donor organs and provide future alternative options in organ replacement therapy. The clinically available tissue-engineered products comprise bradytrophic tissue such as skin, cornea, and cartilage. A sufficient macro- and microvascular network to support the viability and function of effector cells has been identified as one of the main challenges in developing bioartificial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 143 publications
(466 reference statements)
0
7
0
1
Order By: Relevance
“…Some of the limitations of conventional tissue engineering can be overcome using 3D bioprinting. The advantage of 3D bioprinting is its ability to spatially distribute cells within the construct and to design the vasculature within the construct [30]. To achieve the highest level of functional performance in bioprinted constructs, it is necessary to mimic the cell arrangement and microenvironment of the native tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the limitations of conventional tissue engineering can be overcome using 3D bioprinting. The advantage of 3D bioprinting is its ability to spatially distribute cells within the construct and to design the vasculature within the construct [30]. To achieve the highest level of functional performance in bioprinted constructs, it is necessary to mimic the cell arrangement and microenvironment of the native tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are two main ways to promote blood vessel formation: (1) adding pro-angiogenic signaling molecules to the bioink and (2) encapsulating cells that promote blood vessel formation in specific bioinks. 149 The most prominent signaling molecule integrated into bioinks for promoting angiogenesis is vascular endothelial growth factor (VEGF). The optimal dosage of this pro-angiogenic signaling molecule is influenced by various factors, such as the composition of the bioink, cell density, and culture conditions.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…In addition, the extracellular matrix components and binding motifs contained in bioinks can also influence blood vessel formation. 149 For example, research has shown that incorporating the arginine−glycine− aspartic acid (RGD) sequence can promote endothelial cell adhesion and proliferation. This sequence is naturally present in hydrogel materials, such as collagen, fibronectin, and hyaluronic acid.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations